2010
DOI: 10.4038/jrrisl.v88i0.1817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of yields between budgrafts and mother trees in <I>Hevea brasiliensis</I> Muell. Arg.

Abstract: Data available from three experiments conducted during 1939 and 1953 on the dry rubber yield of mother tree genotypes and clones derived from them by bud grafting were analyzed. These experiments comprised of 64 mother genotypes belonging to 23 families. Three to five bud grafted trees have been derived from each of these mother trees within one year and the age difference between the mother trees and clones were about one year. In all three experiments the dry rubber yields in budgrafts from the high yielding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Farmers in the traditional rubber growing areas are cultivating several food crops including tea, bana na, cinnamon, pepper, and pineapple wit h rubber. It is reported that increasing the input efficiency of food crops is vital to minimize competition for resources with rubber and the application of proper agronomic practices is most vital in ensuring the input efficiency of food crops [3]. Adding food crops cultivation to the rubber lands gives more benefits, except for crop yield such as increasing nitrogen availability in soil, reducing soil erosion, and plant support to control crop pests [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Farmers in the traditional rubber growing areas are cultivating several food crops including tea, bana na, cinnamon, pepper, and pineapple wit h rubber. It is reported that increasing the input efficiency of food crops is vital to minimize competition for resources with rubber and the application of proper agronomic practices is most vital in ensuring the input efficiency of food crops [3]. Adding food crops cultivation to the rubber lands gives more benefits, except for crop yield such as increasing nitrogen availability in soil, reducing soil erosion, and plant support to control crop pests [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Kendala yang utama adalah rendahnya intensitas cahaya akibat naungan. Menurut Pathiratna (2006) dan Wibawa et al (2006), intensitas cahaya pada dua tahun pertama penanaman tanaman karet mencapai hampir 100%, namun mengalami penurunan pada tahun ke tiga bersamaan dengan pertumbuhan kanopi tanaman karet.…”
unclassified